Examination of Prior Experience with Telehealth and Comfort with Telehealth Technology as a Moderator of Treatment Response for PTSD and Depression in Veterans. (July 2014) - Price, Matthew; Gros, Daniel F.
Objective: Telehealth is a method to expand the reach of clinical care for PTSD treatment. However, those with limited prior exposure to telehealth or limited confidence using telehealth may have poorer treatment response. The present study examined familiarity with telehealth as a moderator of treatment response for a behavioral treatment delivered via telehealth. Method: Fifty-nine combat veterans completed eight sessions of exposure-based treatment via telehealth. Familiarity with telehealth and confidence in the technology were assessed at baseline. Results: PTSD and depression symptoms decreased as a result of treatment administered via telehealth. Familiarity with the technology and confidence in the technology were unrelated to symptom change. The lack of a significant relation was maintained after controlling for age. Conclusions: Perceptions of telehealth are unrelated to outcomes for mental health treatment. Clinicians should be confident in using this approach with patients, regardless of their familiarity or comfort with the technology.